Urban rail transit : design manual - Vidal, Luis; Yang, Ziyu; Yang, Sun (Hong Kong : Design Media Publishing Limited, 2013)
Stations are places of great significance for passengers and no-travelling users. They serve the growing needs of an increasingly mobile population and are enjoyed by a wide range of users. With millions of journeys made via the urban rail each day, designers should acknowledge the importance of rail passengers. The design guidelines in this book place passengers as the first priority of the design process, bearing in mind that all the elements of station design should be so arrange as to meet their expectations. This book also provides an overview of what established designers consider to be important in the planning and design of metro stations, with considerable number of selected new an extension projects, as well as major reconstruction and maintenance programmes. This book is intended to assist sponsors and project managers through the design and development process. It is hoped that all parties involved in station design and operation can find it informative and inspirational.
engineering bookfair2016
Keywords: Urban transportation; Urban transportation -- Planning; Local transit